Determining an optimal small mining unit for the Twangiza Mine using the Analytic Hierarchy Process - Aboubakar, Bubaka Rudahya (My University, 2022)
Optimising the mineral extraction process for a more profitable operation is crucial for the wealth of a mining company. Mine planners define the smallest mining unit (SMU) during the optimisation process to serve many different factors. These factors include the main orebody indicators such as the size of the mining equipment, the direction of mining, and the depositional environment of the orebody. In this study, the selection of the SMU size for an open-pit mine is discussed. The Twangiza gold deposit in the Democratic Republic of Congo is used as the case study where the drilling database is used to construct five in-situ resource models at the block size of 5x5x2.5m, 7.5x7.5x2.5m, 10x10x5m, 12.5x12.5x5m and 15x15x7.5m. The pit optimisation results coupled with the mining operations factors such as the equipment size and productivity are used to determine the SMU size that best suits the Twangiza north deposit. The average mining grade, the dilution factor, the ore tonnage, the stripping ratio, the project NPV, the environmental impact, the productivity and the life of mine are the primary criteria used to select the best SMU size using the analytical hierarchy process (AHP). The grade-tonnages curves performed on the insitu resource models demonstrate the impact of the SMU on selectivity, which is that as the block dimension gets larger, the average mining grade, the tonnage above the cut-off, and the metal content drop. During pit optimisation, the 5x5x2.5m block provides higher NPV and a larger pit shell. However, the sensitivity study shows that the smaller block size yields an increased dilution factor and cost of selectivity. When these two parameters are also considered in the pit optimisation, the NPV of the smaller SMU size drops at the advantage of the 10x10x5m. When adding the mining parameters to the pit optimisation results to construct an AHP model to select the best alternative, the 10x10x5 remains the SMU that best suits the deposit. Although the study confirms that the SMU of 10x10x5m used at Twangiza is the optimal SMU, it is recommended that the Twangiza mine planners should use a scientific method to determine such vital factors in the mine optimisation.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2022